Addressing Evidence Linking Secondary Alexithymia to Aberrant Humor Processing. (18th July 2019) - Patrikelis, Panayiotis; Lucci, Giuliana; Alexoudi, Athanasia; Korfias, Stefanos; Messinis, Lambros; Nasios, Grigorios; Papasilekas, Themistoklis; Sakas, Damianos; Gatzonis, Stylianos
Abstract : In this review, we explore current literature and assess evidence linking secondary (acquired) alexithymia to aberrant humor processing, in terms of their neurobiological underpinnings. In addition, we suggest a possible common neuropathological substrate between secondary alexithymia and deficits in humor appreciation, by drawing on neurophysiologic and neuroradiological evidence, as well as on a recent and unique single-case study showing the cooccurrence of secondary alexithymia and deficit in humor appreciation. In summary, what emerges from the literature is that the cortical midline structures, in particular the medial prefrontal cortex (mPFC), the anterior cingulate cortex (ACC), and the insular cortex, seem to play a crucial role in the expression of both alexithymia and defective humor processing, while though to a lesser extent, a right hemisphere and bilateral frontoparietal contribution becomes evident. Neurobiological evidence of secondary alexithymia and aberrant humor processing points to the putative role of ACC/mPFC and the insular cortex in representing crucial processing nodes whose damage may produce both the above clinical conditions. We believe that the association of secondary alexithymia and aberrant humor processing, especially humor appreciation deficit, and their correlation with specific brain regions, mainly ACG/mPFC, as emerged from the literature, may be of some heuristic importance. Increased awareness on this topic may be of aid for neurosurgeons when accessing emotion-relevant structures, as well as for neuropsychologists to intensify their efforts to plan evidence-based neurorehabilitative interventions to alleviate the deleterious effects of such interpersonal communication deficits.